The influence of governance to zakat disbursement efficiency in Brunei Darussalam - Ali, Nurul Nabilah; Mohd Alwi, Norhayati; Mohd Ariffin, Noraini (2015)
Purpose – This paper aims to measure the level of zakat disbursement efficiency (ZDE) in Brunei Darussalam from the year 2000 to 2012 and identifies the governance factor(s) that influence efficiency.